Community Based Tourism Development: Studi on Lake Pading Tourism in the Lubuk Besar Sub-Districk Village, Central Bangka Regency - Setya Devy Anggrainy; Aimie Sulaiman; Herdiyanti (Profesional Muda Cendekia Publishing, 2023)
ABSTRACT Community-based tourism development is a tourism model that emphasizes the active role of the community in tourism development. The community is a group of youth who are members of a tourism awareness group organization. The tourism awareness group is Pokdarwis Pelintar Perlang Village, Central Bangka Regency. One of the tours currently being developed is Pading Lake tourism which is a former tin mining area. In this study there is social capital as a strength possessed by youth groups to achieve common goals both socially and economically. Social capital arises in this environment because of the interactions that exist within a group which are influenced by trust, rules or norms and social networks. The aim of this research is to find out and describe the strategy for developing padding lake tourism in Perlang Village, knowing the opportunities and challenges in developing pading lake tourism which of course cannot be separated from the inhibiting factors. This research method uses a descriptive qualitative approach in which there are primary data sources from in-depth interviews with informants. This study took as many as 14 informants with the technique of determining informants using purposive sampling technique. This study uses the theory of Social Capital from Robert Putnam which focuses on three elements, namely trust, norms and social networks. The results of the research show that the development strategy is to develop facilities and infrastructure in the Pading Lake tourist destination area, create business opportunities and tourist attractions (camping ground), improve post-mining land rehabilitation, increase promotion, increase human resources. Then there are inhibiting factors, namely inadequate facilities and infrastructure. Furthermore, the opportunity is to help create business actors. While the challenge is to maintain cohesiveness and convince tourism actors to survive, the ups and downs of visitors. Keywords: Tourism Development, Tourism Awareness Groups, Social Capital